Neutrophil Gelatinase-Associated Lipocalin and Kidney Diseases - Hyung Eun Yim (Korean Society of Pediatric Nephrology, 2015)
Neutrophil gelatinase-associated lipocalin (NGAL) has emerged as one of the most promising biomarkers of renal epithelial injury. Numerous studies have presented the diagnostic and prognostic utility of urinary and plasma NGAL in patients with acute kidney injury, chronic kidney disease, renal injury after kidney transplantation, and other renal diseases. NGAL is a member of the lipocalin family that is abundantly expressed in neutrophils and monocytes/macrophages and is a mediator of the innate immune response. The biological significance of NGAL to hamper bacterial growth by sequestering iron-binding siderophores has been studied in a knock-out mouse model. Besides neutrophils, NGAL is detectable in most tissues normally encountered by microorganisms, and its expression is upregulated in epithelial cells during inflammation. A growing number of studies have supported the clinical utility of NAGL for detecting invasive bacterial infections. Several investigators including our group have reported that measuring NGAL can be used to help predict and manage urinary tract infections and acute pyelonephritis. This article summarizes the biology and pathophysiology of NGAL and reviews studies on the implications of NGAL in various renal diseases from acute kidney injury to acute pyelonephritis.